Does the hysteria exist? 80 years after the death of Sigmund Freud. Disqualification on immunity in modern times - Alcalde Muñoz, Elvis Jorge (2019)
This article provides an overview of the functioning of mental disorder, trying to understand their symptoms and origin, taking special interest in hysterical pictures. At the same time, analyzing in the light of modern times the development that has experienced some disorders of the minds such as neuroses. On the other hand, it addresses the problems in the criminal system, especially the peruvian, and the proclivity to mitigate or exempt criminal sanctions to certain kinds of behaviors derived from psychic disorders.